Pengaruh Variasi Produk, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Toko Ramai Semarang - Muhlidin Muhlidin; Rowiyani Rowiyani; Alfin Muslikhun (Jurnal Akuntan Publik, 2023)
This study aims to determine the effect of product variations on consumer satisfaction Ramai Semarang Store. Inferential level research type. The population in this study are all consumers who shop at Ramai Semarang Store. The sampling technique used the accidental sampling method with a total sample of 100 people obtained using the Lemeshaw formula. The data analysis technique used is multiple regression. The results of this study indicate that product variations have a positive effect on consumer satisfaction at Ramai Semarang Store. Product quality has a positive effect on consumer satisfaction at Ramai Semarang Store. Service quality has a positive effect on consumer satisfaction at Ramai Semarang Store. Testing the feasibility of the model obtained product variations, product quality, and service quality simultaneously affect consumer satisfaction Ramai Semarang Store.